The Influence of Legal Culture on Business Actors' Compliance in Hazardous Cosmetic Products in Indonesia - Elsi Kartika Sari; Sofia; Dede Mulyanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of legal culture on business actors' compliance in producing cosmetics that are safe and free from hazardous materials. Legal culture that includes norms, values ​​and traditions in the application of law has an important role in determining the level of business actors' compliance with existing regulations. In the context of the cosmetics industry, compliance with regulations is highly dependent on legal awareness, effective supervision, and strict sanctions for violations. A strong legal culture accompanied by an understanding of business ethics and consistent law enforcement can encourage business actors to prioritize consumer safety. Conversely, a weak or ineffective legal culture tends to reduce the seriousness of business actors in complying with safety standards that can pose a risk to public health. The formulation of the problem obtained from this study is How is business actors' compliance with hazardous cosmetic regulations? ⁠And how is the BPOM regulation for hazardous cosmetics in Indonesia?. Therefore, a supportive legal culture and a strict law enforcement system are very important in creating a safe and sustainable cosmetics industry. This study is expected to provide a deeper understanding of the relationship between legal culture and compliance of cosmetic business actors.